Atlas of the Odonata of western Sicily - Salvatore Surdo (Natural History Sciences)
Given their sensitivity to environmental alterations, odonates act as reliable bioindicators of possible changes in freshwater ecosystems and associated terrestrial habitats. The geographical area spanning from Carini to Trapani and Sciacca (Provinces of Palermo, Trapani, and Agrigento - Sicily, Italy) is largely urbanized, and its territory is heavily altered, especially in proximity to the seacoast at low altitude. Despite this pervasive anthropization, the area is still characterized by a variety of freshwater habitats, possibly harboring rich odonate assemblages that, however, have never been thoroughly investigated. This study, aimed at producing the first commented checklist of the Odonata of this area enriched by distribution maps, is based on 2951 records, derived from the literature (n=293), citizen-science projects (n=102), and unpublished data mainly collected by the author and spanning from 2015 to 2023 (n=2556). Despite being densely populated, strongly urbanized, agriculturally exploited, and characterized by scarce and altered heterogeneous freshwater habitats, the geographical area encompassed in this study still hosts a remarkable diversity of Odonata. Indeed, 39 species observed in the study area represent almost half (41%) of the species ever recorded in Italy (n=95) and 27% of those recorded in Europe (n=146). Despite extensive research, two species reported in the bibliography, namely Lestes dryas and Aeshna cyanea have not been contacted.